Addressing Self-Harm in Paranoid Schizophrenia: The Role of Supportive Psychotherapy in Primary Health Care - Abdillah, Diaz Syafrie; Mumpuni, Yekti; Algristian, Hafid; Azizah, Nur; Khairunnisa (Indonesian Scientific Publication, 2025)
Self-harm represents a serious psychiatric emergency frequently observed in individuals with schizophrenia, especially the paranoid subtype, where hallucinations, delusions, and comorbid depression play crucial roles. Although antipsychotic medications remain the cornerstone of treatment for symptom stabilization, they are often insufficient to address underlying psychosocial vulnerabilities that heighten self-harm risk. Supportive psychotherapy (SPT) has emerged as a cost-effective adjunctive intervention that can be integrated within primary health care to complement pharmacological treatment. This literature review synthesizes studies published between 2011 and 2025, retrieved from PubMed, ScienceDirect, and Google Scholar using the keywords paranoid schizophrenia, supportive psychotherapy, and self-harm. Findings reveal that SPT, when implemented after acute psychotic symptoms have subsided, enables patients to express emotions, receive reassurance, and modify maladaptive thoughts through supportive persuasion. Evidence indicates that SPT effectively reduces suicidal ideation and self-harm severity, commonly assessed using the Suicidal Intention Rating Scale (SIRS). Additionally, involving families and providing psychoeducation improve treatment adherence, reduce relapse rates, and create a more supportive home environment. Compared to structured psychotherapies such as cognitive behavioral therapy (CBT) or family-focused therapy (FFT), SPT is simpler, more flexible, and feasible in low-resource settings since it can be delivered by general practitioners with basic training. Overall, this review concludes that SPT offers significant potential to mitigate psychiatric emergencies and enhance the quality of life in paranoid schizophrenia patients at risk of self-harm. It recommends training primary care providers in SPT, integrating family psychoeducation, and implementing a stepped-care model that positions SPT as an initial stabilization phase before advancing to structured therapies.